ASSESSMENT OF HAND HYGIENE COMPLIANCE AMONG HEALTHCARE WORKERS IN INTENSIVE CARE UNITS OF NISHTAR HOSPITAL, MULTAN: AN OBSERVATIONAL STUDY (Journal of Medical & Health Sciences Review, 2025)
Background: Hand hygiene remains the cornerstone of infection prevention, particularly in high-risk areas such as intensive care units (ICUs), where patients are more vulnerable to healthcare-associated infections (HAIs). Despite established WHO guidelines, hand hygiene compliance among healthcare workers continues to be suboptimal in many settings.Objective: This study aimed to assess the level of hand hygiene compliance among healthcare workers in the ICU of a Nishtar Hospital, Multan.Methods: A prospective observational study was conducted over 6 months, from March 2024 to August 2024, including one month for piloting in the ICU of Nishtar Hospital, Multan. All 49 doctors and nurses from the ICU were included through universal sampling. Hand hygiene was covertly observed by a trained observer who had no direct contact with patients using the WHO’s “Five Moments for Hand Hygiene” through a CDC-standardized checklist.Results: The overall hand hygiene compliance varied across shifts. The morning shift showed the highest compliance with a mean score of 4.49 ± 0.98, followed by the night shift at 3.67 ± 1.05, and the evening shift at 2.67 ± 0.97. The range of compliance scores was 3.00–4.00 across all shifts. The 33rd and 66th percentiles for each shift were as follows: Morning shift: P33 = 5.00, P66 = 5.00, Evening shift: P33 = 2.00, P66 = 3.00, Night shift: P33 = 3.00, P66 = 4.00. These findings indicate higher compliance in the morning shift, possibly due to increased staff availability and supervision. Lower adherence in the evening and night shifts may be associated with fatigue, reduced staffing, or limited monitoring.Conclusion; Hand hygiene compliance among ICU healthcare workers demonstrated significant variation across shifts and remained below optimal standards, especially in evening and night hours. Continuous surveillance, targeted shift-based interventions, and reinforcement strategies are essential to improve adherence and reduce infection risks in critical care settings.